First Day - Mackall, Dandi Daley (New York Harcourt, 2003)
The first day of school starts out filled with doubt, but after facing fear of the big kids, reciting the alphabet with ease, and learning about recess, a child can't help but look forward to day two.
K - 2
Keywords: First day of school; School stories; Stories in rhyme